2012
DOI: 10.3113/fai.2012.0857
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous and Extraosseous Arterial Anatomy of the Adult Navicular

Abstract: If diminished vascular supply is a contributing factor to navicular stress fracture, our results suggest that a relatively small proportion of individuals is prone to their development. Biomechanical or other clinical factors may play a more prominent role in the development of navicular stress fractures than previously suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 16 publications
(16 reference statements)
0
29
0
1
Order By: Relevance
“…Golano et al [3] also showed osteonecrosis or stress fractures can affect the navicular bone because of its poor vascularization, especially in its central portion. But, a study done by McKeon et al [17] on vascularity of navicular bone using modified Spälteholz technique showed that the navicle had a dense intraosseous vascular supply throughout and only 11% bones had an avascular central zone.…”
Section: Discussionmentioning
confidence: 99%
“…Golano et al [3] also showed osteonecrosis or stress fractures can affect the navicular bone because of its poor vascularization, especially in its central portion. But, a study done by McKeon et al [17] on vascularity of navicular bone using modified Spälteholz technique showed that the navicle had a dense intraosseous vascular supply throughout and only 11% bones had an avascular central zone.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the stresses are concentrated in the relatively least vascular area of the bone. This arterial anatomy has since been in question, as McKeon et al 8 found a dense intraosseous vascular supply in most adult cadaveric specimens, which may indicate that other biomechanical or other risk factors may predispose the navicular to a stress injury.…”
Section: Navicular Stress Fracturesmentioning
confidence: 95%
“…The dorsalis pedis and posterior tibial arteries supply blood to the navicular bone. 8 The zone of avascularity in the central one-third of the bone was first described by Waugh 9 in a study of adolescents. Therefore, the stresses are concentrated in the relatively least vascular area of the bone.…”
Section: Navicular Stress Fracturesmentioning
confidence: 99%
“…A mean delay of four months between the onset of symptoms and diagnosis demonstrates the difficulty of making the diagnosis, likely contributed to by a 66% false negative rate on plain X-rays and the need for CT or MRI [28]. Physiologically the navicular may be predisposed to stress fractures through the presence of a relatively avascular watershed in the central third of the bone, although cadaveric examinations have questioned the significance of this finding [29].…”
Section: Navicularmentioning
confidence: 98%